A Family of high-frequency isolated single-phase AC-AC converters - Silva Filho, Olympio Cipriano da (2019)
A family of single-phase AC-AC converters isolated at high frequency is proposed. A set of common active and passive elements is shared by all topologies of the family and is based on the interleaved inductors and the DAB (Dual Active Bridge) converter. This enables high power density and current capacity, as well as smooth switching in part of the semiconductors. The family consists of nine topologies being three symmetrical and six asymmetrical. All topologies are described, modeled and simulated. The dynamic performance is checked against voltage sag and load step. Mathematical analysis and simulations showed that differences between the switching functions applied to the switches, which define the primary and secondary voltages of the transformer, increase the circulation current and, consequently, the losses. This problem is minimized in part of the converters of the family that can use the proposed partial actuator scheme. In addition, the currents in the transformer were minimized in some asymmetrical converters through two new modulation schemes. In order to reduce the total magnetic volume and losses, methods for magnetic integration and modeling were studied. As a result, two integrated magnets were developed and tested for the Symmetric Full-bridge converter. At the University of Kassel, an experimental platform was developed with which results were obtained for five topologies. The results showed a good dynamic response of all evaluated converters. In addition, the integration brought a reduction in the total volume of the magnets and an increase in the efficiency of the tested converter.